Mudie’s Select Library and the Three-Decker Novel – A Mutual Failure? - Kroesing, Nina (Satura, 2020)
One of the most successful circulating libraries in 19th-century Britain was Charles Edward Mudie’s Select Library, which opened in 1842. As an important cultural institution, it satisfied the demand of a people that were becoming increasingly literate. For an annual subscription fee of one guinea, readers could borrow one volume at a time. The three-decker, for which Mudie got a discount of up to fifty percent of the nominal price, was his preferred publication format. During the course of this article I will examine the failure of the threedecker system through the writing of contemporary author George Gissing, supported with the work of book historians. I will argue how the three-volume novel that once proved so profitable for the Select Library resulted in Mudie’s eventual business failure and that Mudie’s deliberately decided to kill the format off entirely.